Lobar Dementia due to Extreme Widening of Virchow-Robin Spaces in One Hemisphere - Buerge, Christine (S. Karger AG, 2011)
Widened perivascular spaces known as Virchow-Robin spaces (VRS) are often seen on MRI and are usually incidental findings. It is unclear if enlarged VRS can be associated with neurological deficits. In this report, we describe a case of lobar dementia associated with unusual VRS widening in one cerebral hemisphere. A 77-year-old woman, seen at a memory clinic, presented with progressive cognitive decline, left hemianopsia, and mild pyramidal signs on the left side. On MRI, unusually wide VRS were visible, predominantly in the right centrum semiovale and the right temporo-occipital white matter. The clinical syndrome was consistent with the extent and location of the abnormally dilated VRS. The high MR signal in white matter bridges between the VRS suggested parenchymal damage, possibly representing gliotic white matter. No evidence for another etiology was found on cerebral MRI and rCBF SPECT. As a conclusion, enlarged VRS in one cerebral hemisphere may be associated with cognitive change and neurological deficits.